Estudo comparativo do uso de géis e emulsões na limpeza de tintas de emulsão acrílica - Oliveira, Aline Assumpção de (2022)
This dissertation evaluates the effects of selected gels and emulsions, namely agar, gellan gum, xanthan and Pemulen® TR-2, in the cleaning of acrylic emulsion paints. The selected materials represent alternatives to methodologies traditionally used in the cleaning of paintings and seek to overcome current specific problems in the cleaning of acrylic paintings. Cleaning is one of the most common activities within conservation and restoration treatments, and still, one of the processes that offers great risk to the integrity of the artwork because it is intrinsically irreversible. The search for cleaning systems that reduce the amount of solvent/water used in treatments, and at the same time the sensitivity of acrylic emulsion paints to certain cleaning systems encourages the research for alternative methodologies, which are effective in their purpose and offer less risk to the health of professionals and to pictorial surfaces, with a lower environmental impact. Gellified systems offer greater control over the cleaning action and may represent good alternatives for the cleaning of acrylic paintings. The aim of this work is to comparatively analyse the effectiveness of action of the selected materials and their influence on the original pictorial layer. Tests were performed on mock-ups and results were analysed to perceive cleaning efficiency, presence of residues, paint sensitivity and colour alterations of the pictorial layer. These parameters were evaluated with the aid of digital microscopy, photography, FORS, spectrophotometry, and ATR-FTIR spectroscopy. Tests showed that xanthan gum and Pemulen® gels had better dirt removal efficiency and better adaptability to surface irregularities. Resulting colours after cleaning were more similar to the ones in the control samples. However, these gels resulted in greater pigment removal. Agar and gellan gum rigid gels presented greater control in water diffusion and appear to be more suitable for water-sensitive surfaces. Application time and rinsing variables also influenced results obtained with each material.